Resistance Mechanisms to BCMA Targeting Bispecific Antibodies and CAR T-Cell Therapies in Multiple Myeloma - Brandon Tedder; Manisha Bhutani (Cells, 2025)
B-cell maturation antigen (BCMA)-targeted therapies including both chimeric antigen receptor (CAR) T-cell therapies and bispecific antibodies (BsAbs), have revolutionized the treatment landscape for relapsed/refractory multiple myeloma (MM), offering both deep and durable responses, even in heavily pretreated patients. Despite these advances, most patients ultimately experience relapse. This is likely related to the development of resistance mechanisms that limit the long-term efficacy and durability of BCMA-targeted approaches. In this review, we examine the current landscape of BCMA-directed therapies, including Idecabtagene Vileucel, Ciltacabtagene Autoleucel, Teclistamab, and Elranatamab and explore the multifactorial mechanisms driving resistance. These mechanisms include tumor-intrinsic factors, host-related and tumor-extrinsic factors, and factors related to the tumor-microenvironment itself. We outline emerging strategies to overcome resistance, such as dual-targeting therapies, γ-secretase inhibitors, immune-checkpoint blockade, armored CAR T constructs, and novel combination regimens. Additionally, we discuss the role of therapy sequencing, emphasizing how prior exposure to BsAbs or CAR T-cell therapies may influence the efficacy of subsequent treatments. A deeper understanding of resistance biology, supported by integrated immune and genomic profiling, is essential to optimizing therapeutic durability and ultimately improve patient outcomes for patients with MM.